Difference in Intraocular Pressure Before and After Cataract Surgery with Glaucoma Complications at Kendari Eye Clinic - Amiruddin Eso; Deni Sastra Mandarin; Melvin Manuel Philips (MEDULA: Jurnal Ilmiah Fakultas Kedokteran Universitas Halu Oleo, 2025)
Background: Cataracts and glaucoma are the leading causes of irreversible blindness worldwide and frequently coexist in elderly populations. Cataract-induced structural changes in the anterior segment may impair aqueous humor outflow, resulting in elevated intraocular pressure (IOP) and accelerated optic nerve damage in patients with glaucoma. Purpose(s): This study aimed to analyze differences in IOP before and after cataract surgery among patients with glaucoma complications at Kendari Eye Clinic. Methods: An observational analytic study with a pre–post cross-sectional design was conducted using medical record data from January to June 2024. A total of 100 patients with senile cataracts complicated by glaucoma who underwent phacoemulsification were included using purposive sampling. IOP measurements were obtained using a non-contact tonometer before surgery and at 3 days, 5 days, 12 days, and 1 month postoperatively. Data were analyzed using the Friedman test. Results: The results demonstrated a statistically significant difference in IOP before and after surgery (p < 0.001). Mean IOP increased transiently at 3 days postoperatively but decreased significantly at subsequent follow-up intervals. Conclusion: Phacoemulsification cataract surgery significantly reduces IOP in patients with glaucoma complications, emphasizing its role not only in visual rehabilitation but also in IOP control and glaucoma management.